2011
DOI: 10.1111/j.1476-5381.2011.01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with angiotensin‐(1‐7) improves renal endothelial dysfunction in apolipoproteinE‐deficient mice

Abstract: BACKGROUND AND PURPOSE ApolipoproteinE‐deficient [apoE (−/−)] mice, a model of human atherosclerosis, develop endothelial dysfunction caused by decreased levels of nitric oxide (NO). The endogenous peptide, angiotensin‐(1‐7) [Ang‐(1‐7)], acting through its specific GPCR, the Mas receptor, has endothelium‐dependent vasodilator properties. Here we have investigated if chronic treatment with Ang‐(1‐7) improved endothelial dysfunction in apoE (−/−) mice. EXPERIMENTAL APPROACH ApoE (−/−) mice fed on a lipid‐rich We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 39 publications
4
36
2
Order By: Relevance
“…After 6 weeks, apoE(−/−) mice (groups 2 and 3) were treated with either saline or Ang(1-7) (82 µg/kg per hour) via osmotic mini pumps subcutaneously, as described previously. 24 Another group of apoE(−/−) mice was treated with a p38 MAPK inhib itor (BIRB796, 50 mg/kg per day) from the age of 6 weeks (group 4). In addition, Mas(−/−)/apoE(−/−) doubleknockout mice (groups 5 and 6) were treated as groups 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After 6 weeks, apoE(−/−) mice (groups 2 and 3) were treated with either saline or Ang(1-7) (82 µg/kg per hour) via osmotic mini pumps subcutaneously, as described previously. 24 Another group of apoE(−/−) mice was treated with a p38 MAPK inhib itor (BIRB796, 50 mg/kg per day) from the age of 6 weeks (group 4). In addition, Mas(−/−)/apoE(−/−) doubleknockout mice (groups 5 and 6) were treated as groups 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…7,27,30 Previously, we showed that apoE(−/−) fed on a highfat diet exhibit impaired endo thelialdependent vasorelaxation. 24 Chronic Ang(1-7) treat ment improved NO bioavailability and, therefore, ameliorated endothelial dysfunction in these mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, deletion of the receptor Mas resulted in blood pressure increase and endothelial dysfunction (14) whereas Ang-(1-7) infusion improved vascular function by inducing nitric oxide and prostaglandin release (15)(16)(17). Moreover, Ang-(1-7) has been shown to reduce reactive oxygen species production and vascular inflammation, thereby slowing down the progression of atherosclerosis in mice (18). Although many studies have indicated a clear role of the Ang-(1-7)/Mas axis in vascular inflammation, not much is known about the influence of Mas on immune cells and their function during inflammatory processes.…”
mentioning
confidence: 99%